ANALISIS MEKANISME GOOD CORPORATE GOVERNANCE (GCG) DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN AUTOMOTIF DI BURSA EFEK INDONESIA (BEI) - Pipit Buana Sari (Jurnal Akuntansi Bisnis dan Publik, 2019)
This study aims to find out, analyze and test the effect of good corporate governance (GCG) and firm size on earnings management in Automotive Companies on the Indonesia Stock Exchange (IDX).The period of data taken by the author is 2013-2017. This study uses quantitative descriptive with the support of panel regression which are used as predictive analysis tools.The sampling technique using a non probability random sample with a purposive sampling method using certain criteria to obtain a sample of 12 companies that fit the criteria. The results of this study indicate that independent commissioners, audit committees, institutional ownership and managerial ownership partially / individually have a significant effect on company size. The independent board and audit committee partially / individually have a significant effecton earnings management while institutional ownership and managerial ownership partially / individually do not have a significant effect on earnings management. Independent boards, audit committees, institutional ownership, managerial ownership, and company size significantly influence panel earnings management in ASII, AUTO, BRAM, GDYR, GJTL, IMAS, INDS, LPIN, MASA, NIPS, PRAS and SMSM.